2012
DOI: 10.1007/s11259-012-9547-5
|View full text |Cite
|
Sign up to set email alerts
|

Mouse model of haemorrhagic septicaemia: dissemination and multiplication of Pasteurella multocida B:2 in vital organs after intranasal and subcutaneous challenge in mice

Abstract: Haemorrhagic septicaemia (HS) is an endemic disease of bovines, occurring in most tropical regions of Asia and Africa. In the present study, the suitability of using mice to study pathogenesis of HS was assessed using mortality, mean death time and bacterial multiplication in vital organs after infection with live P multocida. Mice were infected with 10(5), 10(3) and 10(1)cfu of P. multocida B:2 via intranasal and subcutaneous routes along with control groups. Bacterial multiplication in lung, liver and spleen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…Recently, a mouse model of HS caused by P. multocida serotype B:2 has been developed (222), which might enable further exploration of the roles of different host immune cells and host factors as well as bacterial factors in dissemination of the bacteria in the host.…”
Section: Pasteurellosis and Hemorrhagic Septicemiamentioning
confidence: 99%
“…Recently, a mouse model of HS caused by P. multocida serotype B:2 has been developed (222), which might enable further exploration of the roles of different host immune cells and host factors as well as bacterial factors in dissemination of the bacteria in the host.…”
Section: Pasteurellosis and Hemorrhagic Septicemiamentioning
confidence: 99%
“…Earlier, Abdullah et al (2013b) had reported the successful recovery of P. multocida using PCR from various organs of mice inoculated with contaminated river water. HS is a deadly infection and the extent of lesion manifestation depends on the duration of the disease and the dose of bacterial inoculums (Kharb and Charan, 2013). This is in line with the findings of this study, where moderate and severe lesions were observed following inoculation with contaminated water that had stayed for 72 h in comparison to lesions observed following inoculation with contaminated water that had stayed for 24 and 48 h. This shows that the P. multocida was more active at 72 h post contamination, perhaps due to decomposition of the mice carcass and shedding of the bacteria into the water.…”
Section: Discussionmentioning
confidence: 99%
“…The organism is the etiological agent of Haemorrhagic septicaemia in cattle and water buffalo and it is predominant in South and South East Asia and to most parts of tropical Africa (Abubakar and Zamri-Saad, 2011;Kharb and Charan, 2013;Khaleel et al, 2013;Abdullah et al, 2013a;Jesse et al, 2013a;. HS is a peracute disease and is considered to be one of the most economically important diseases in Asia particularly in South and South East Asia leading to huge economic loss in livestock industry (Jesse et al, 2013a).…”
Section: Intoductionmentioning
confidence: 99%
“…There are several disease models of infection with P. multocida using mice and show the suitability of mice to study the pathogenesis of P. multocida to produce HS with same symptoms and lesion in cattle and water buffalo (Affandi et al, 2012;Jamal et al, 2013;Faez et al, 2013). In pure chemical form endotoxin is a Lipopolysaccharide (LPS) which has widely variable composition (or chemotype) and exerts a wide range of often opposing influences on host pathogen interactions (Khaleel et al, 2013;Kharb et al, 2013). The key virulence factors identified in Pasteurella multocida type B: 2 include capsule, lipopolysaccharides, surface adhesions, ironregulated and iron acquisition proteins (Affandi et al, 2012;Kharb et al, 2013).…”
Section: Intoductionmentioning
confidence: 99%
See 1 more Smart Citation